The lung microbiome of Human Immunodeficiency Virus-infected patients with active pulmonary Mycobacterium tuberculosis infection - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2022)
Thesis (PhD (Internal Medicine))--University of Pretoria, 2021.